A Major Facilitator Superfamily Transporter Regulated by the Stress-Responsive Transcription Factor Yap1 Is Required for Resistance to Fungicides, Xenobiotics, and Oxidants and Full Virulence in Alternaria alternata - Lin, Hsien-Che; Yu, Pei-Ling; Chen, Li-Hung; Tsai, Hsieh-Chin; Chung, Kuang-Ren (Frontiers in Microbiology, 2018)
Alternaria alternata relies on the ability to produce a host-selective toxin and to detoxify reactive oxygen species to successfully colonize the host. An A. alternata major facilitator superfamily transporter designated AaMFS54 was functionally characterized by analysis of loss- and gain-of-function mutations to better understand the factors required for fungal pathogenesis. AaMFS54 was originally identified from a wild-type expression library after being subtracted with that of a mutant impaired for the oxidative stress-responsive transcription regulator Yap1. AaMFS54 contains 14 transmembrane helixes. Fungal mutant lacking AaMFS54 produced fewer conidia and increased sensitivity to many potent oxidants (potassium superoxide and singlet-oxygen generating compounds), xenobiotics (2,3,5-triiodobenzoic acid and 2-chloro-5-hydroxypyridine) and fungicides (clotrimazole, fludioxonil, vinclozolin and iprodione). AaMFS54 mutant induced necrotic lesion sizes similar to those induced by wild-type on leaves of a susceptible citrus cultivar after point inoculation with spore suspensions. However, the mutant produced smaller colonies and less fluffy hyphae on the affected leaves. Virulence assays on citrus leaves inoculated by spraying with spores revealed that AaMFS54 mutant induced less severe lesions than wild-type, indicating the requirement of AaMFS54 in pathogenesis. All defective phenotypes were restored in a strain re-acquiring a functional copy of AaMFS54. Northern blotting analysis revealed that the expression of AaMFS54 was suppressed by xenobiotics. The studies indicate that the Yap1-mediated transporter plays a role in resistance to toxic oxidants and fungicides in A. alternata. The relationships of MFS transporters with other regulatory components conferring stress resistance and A. alternata pathogenesis are also discussed.